A review study on sustainable utilisation of waste in bituminous layers of flexible pavement - Mohit Nandal; Hemant Sood; Pardeep Kumar Gupta (Case Studies in Construction Materials, 2023)
The development of a new road has a variety of ramifications for the environment, using considerable quantity of materials and energy. Also, the cost of crude oil, which is the principal source of bituminous binder, has substantially grown in recent years. This has resulted to a rise in the overall price of bituminous blends. Developing innovative materials and technology to incorporate greener material, waste and recycled materials into the manufacturing cycle of bituminous mixes is a solution that enhances both sustainability and cost-efficiency of the bituminous pavement industries. Sustainable materials have increasingly been adopted in construction of roads nowadays because people are more concerned about its ramifications towards surroundings. However, people keep seeking to discover the most appropriate sustainable materials to be utilised in developing road pavement. In the current research, the two primary components of bituminous mixture i.e. bitumen and aggregates are focused and reviewed. Furthermore, the study presents a brief outline of several recycled materials which have been effectively used into bituminous layers of flexible pavement. Review findings suggest that the usage of secondary material not only offers an effective waste disposal approach but also minimise requirement for traditional material and lowers the total building cost. An effective and appropriate system of transportation is crucial for the development of any nation. The purpose of this review study is to establish the applicability and effectiveness of the waste material that has been used in the bituminous layers of flexible pavement.